Three new species of the family Phthiracaridae (Acari, Oribatida) from Bolivia - Niedbała, Wojciech; Starý, Josef (Zootaxa, 2015)
Three new species of the family Phthiracaridae, Austrophthiracarus longisetosus sp. nov., Phthiracarus allocotos sp. nov., Protophthiracarus amboroensis sp. nov. from Bolivia are described and figured. A comparison of morphological similarities with the most closely related species is presented. Additional descriptions and taxonomical notes for three ptyctimous species: Acrotritia peruensis (Hammer, 1961), Acrotritia vestita (Berlese, 1913), and Steganacarus (Rhacaplacarus) sedecimus Niedbała, 2004 are added. A list of twenty six ptyctimous species from Bolivia is presented, ten of these species are new records for the fauna of Bolivia. A key to all species of ptyctimous mites of Bolivia is presented.